Multi-Objective Optimization for Uncertainty Management in Circular Economy: An Empirical Approach to the Yellow Tofu Industry in Kediri - Ana Komari; Lolyka Dewi Indrasari (Universitas Muhammadiyah Sidoarjo, 2026)
The small and medium-scale tofu industry faces production efficiency and waste management issues that impact economic and environmental performance. This study aims to optimize yellow tofu production by maximizing profits, minimizing raw material waste, and optimizing waste utilization into economically valuable products. The Multi-Objective Linear Programming (MOLP) approach is used to model the production system by considering the limitations of raw materials, production capacity, and working hours. Fishbone Diagram analysis is applied to identify factors causing waste generation based on human, machine, material, method, environment, and management aspects. The optimization results show that the optimal production of yellow tofu reaches 1,194.03 kg/day with an objective value of Rp 7,164,179, where the constraints of working hours and the use of turmeric are in binding conditions. The integration of waste utilization allows tofu dregs to be fully utilized as a by-product of 5.01 kg/day, so that net waste can be reduced to zero. The feasibility evaluation of a circular economy using NPV, IRR, B/C, and Payback Period shows that waste utilization is financially feasible. This research contributes to the formulation of efficient, sustainable, and environmentally friendly tofu production strategies for small and medium industries.